UTJECAJ MOTORIČKIH SPOSOBNOSTI I KONATIVNIH REGULATIVNIH MEHANIZAMA NA REZULTATSKU USPJEŠNOST U SPORTSKIM IGRAMA - Fuad Ražanica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
In order to establish the relations and the amount of influence of some motoric abilities as well as some conative regulatory mechanisms on the success in performance situational - motoric tests in sports games a group of 127 students, aged 15-17, of ''Mješovita srednja škola'' Ilijaš has been tested and the results obtained in sports games has been analyzed. Eight tests (complied with EUROFIT) which are to observe five latent, hypothetically defined motoric dimensions were applied in the field of motoric abilitiesAs the measuring instruments the most used scales for evaluation of conative characteristics were: Anxiety, Inhibitory conversion, Aggressivity and Schizoifrenic disorders Twelve tests of situational motoric in four sports games: basketball, volleyball, football and handball were applied in the field of situational-motoric abilities. The results of regressive analysis lead to conclusion that the success in sports games is directly determined by the abilities which are under the influence of energetic mechanisms and abilities based on efficiency of movement regulation. In the field of conative regulatory mechanisms none of Beta coefficients is obtained in certain significancy.